Annual World Bank Conference on Development Economics 2003 : the new reform agenda - The World Bank; Pleskovic, Boris; Stern, Nicholas; The World Bank (Washington, D.C. : The World Bank, 2003)
The Annual World Bank Conference on Development Economics (ABCDE) contains the works of World's leading scholars and development practitioners in development policy and the implication for the global economy. The book is the 14th conference which addressed four timely and important themes in development: trade and poverty, Africa's future in terms of industrial and or agricultural development, education and empowerment, and investment climate and productivity.
includes bibliography references pp.312-313.
usc 14/06/17
Ref.
Keywords: Development economics; Reform agenda; Developing countries